Report of the Committee on the Elimination of Discrimination against Women, Sixty-eighth Session - United Nations Department for General Assembly; Conference Management (United Nations, 2013)
This is the annual report submitted to the General Assembly by the Committee on the Elimination of Discrimination against Women on its activities for the fifty-second session, fifty-third session, and fifty-fourth sessions.